Effects of incubation time and temperature on microbiologic sampling procedures for hemodialysis fluids. - Arduino, M J (1991)
To prevent pyrogenic reactions and bacteremia in hemodialysis patients, the Association for the Advancement of Medical Instrumentation and the Centers for Disease Control recommend culturing of hemodialysis fluids (water and dialysate) at least once a month. The recommendations for total microbial counts are (i) less than or equal to 200 CFU/ml in water used to prepare dialysate or reprocess hemodialyzers and (ii) less than or equal to 2,000 CFU/ml for the dialysate. In accordance with the Association for the Advancement of Medical Instrumentation recommendations all cultures should be incubated at 37 degrees C for 48 h on suitable culture media, such as Trypticase soy agar, standard methods agar, or one of several commercially available assay systems. There have been suggestions that lower temperatures and longer incubation might improve the recovery of bacteria from water and dialysate. In this study bacterial recovery from various dialysis fluids (water, bicarbonate dialysate, and bicarbonate concentrate) at 30 and 37 degrees C was compared. Duplicate sets of samples were membrane filtered (pore size, 0.45 microns); one set was incubated at 30 degrees C and the other was incubated at 37 degrees C for 72 h. The number of visible colonies was counted every 24 h by using a dissecting microscope. No significant difference was observed in specimens incubated at 37 degrees C for 48 h compared with those incubated at 30 degrees C for 72 h. Also, bacterial recovery was significantly better when samples of bicarbonate dialysate or bicarbonate concentrate were plated on Trypticase soy agar as opposed to standard methods agar.